Study on Spin-orbit Torque-induced Magnetization Switching in a Ferrimagnetic GdFeCo/Pt Using Complementary Electric and Optical Measurements - Kim, Seong Tae; Jeong, Yun-Chae; Kim, Duck-Ho; Je, Soong-Geun (한국자기학회, 2024)
We carried out spin-orbit torque (SOT) induced magnetization switching experiments in a ferrimagnetic GdFeCo/Pt with perpendicular magnetic anisotropy. To clearly understand the magnetization switching in the GdFeCo/Pt Hall bar structure, we investigated the magnetization switching phenomena via electric and optical techniques, such as the anomalous Hall measurement and simultaneously the magneto-optical Kerr effect imaging. It is found that the SOT-induced switching is accomplished via the local nucleation of domains and domain wall motions. It is also observed that the anomalous Hall signal due to spin-orbit torque was slightly smaller compared to that of the magnetic field-induced reversal. We confirm that the smaller signal is due to the incomplete magnetization switching in the Hall bar.